Clinico-moleculo-pathological Conference (CMPC): A Clinical Teaching Method to optimise knowledge integration and collaboration in the workplace-based specialist education - Bekti, Rachmad Sarwo; Seputra, Kurnia Penta (Universitas Gadjah Mada, 2025)
Integrating current molecular knowledge and research with real-world clinical and pathological conditions is a critical step in finding the most appropriate approach for modern and personalized patient care. A modified clinicopathological conference, called the Clinico-molecular-pathological conference (CMPC), was introduced in one out of five introductory specialist training courses at our teaching hospital. It is intended to enhance the application of basic biomedical sciences, particularly biomolecular aspects, in integrated clinical care and personalised medicine. We attempted to analyse the CMPC’s implementation and its educational impact from the perspectives of trainees through a program evaluation activity adopting the first two levels of the Kirkpatrick Pyramid. From 4 batches (2022-2024), 433 out of 447 residents (96.87% response rate) responded to our online program evaluation questionnaire. From the reaction and learning level, the CMPC has convincingly been favoured by residents as an engaged learning method for elaborating basic medical sciences, especially biomolecular topics, into a real clinical and patient care context. Despite the poor correlation of the course’s overall satisfaction to the CMPC mark and final course marks (p>0.05), there is a positive and significant correlation between CMPC mark and Course Final mark (r=0.39; p=0.00). Qualitative response to the survey triangulated the acceptance of CMPC as a promising learning method to promote integrated learning as well as multidisciplinary collaboration. The case study provides insight into how CMPC is favoured by the residents to learn difficult subjects, and is related to academic achievement. CMPC is also perceived to be a promising method to promote integration in patient care in medical specialist education. Further research is needed to optimise both the educational and quality service impact of the CMPC in the workplace-based medical specialist education.